Potato Cv. ‘Granola’ Has Moderate Tolerance for Bacterial Wilt Disease - Gashaw Belay Alemu; Jake A. Criscuolo; Charlie Higgins; Caitilyn Allen (American Journal of Potato Research, 2025)
Bacterial wilt or brown rot caused by Ralstonia solanacearum is among the most destructive diseases of potato in tropical highlands worldwide. There are no completely wilt-resistant varieties, but growers can reduce losses by planting partially resistant or tolerant potatoes. We screened the popular tropical potato cv. ‘Granola’ for bacterial wilt resistance under controlled conditions. Granola plants inoculated with high doses of R. solanacearum IIB-1 (Race 3 biovar 2) had reduced wilt disease progress relative to susceptible control cv. ‘Russet Norkotah’. Although the pathogen did colonize Granola plants, it reached significantly lower population sizes in Granola stems, stolons, and especially tubers than in those of Russet Norkotah. These results suggest that Granola has some tolerance to bacterial wilt, likely mediated by suppression of bacterial colonization. Thus, Granola could be a useful parent for tropical potato breeding programs.

Workflow to facilitate the detection of new psychoactive substances and drugs of abuse in influent urban wastewater - Richard Bade; Denice van Herwerden; Nikolaos Rousis; Sangeet Adhikari; Darren Allen; Christine Baduel; Lubertus Bijlsma; Tim Boogaerts; Dan Burgard; Andrew Chappell; Erin M. Driver; Fernando Fabriz Sodre; et al. (Journal of Hazardous Materials, 2024)

Adaptation and early implementation of the PREdiction model for gene mutations (PREMM5™) for lynch syndrome risk assessment in a diverse population - Kathleen F. Mittendorf; Chinedu Ukaegbu; Marian J. Gilmore; Nangel M. Lindberg; Tia L. Kauffman; Donna J. Eubanks; Elizabeth Shuster; Jake Allen; Carmit McMullen; Heather Spencer Feigelson; Katherine P. Anderson; Michael C. Leo; et al. (Familial Cancer, 2022)
Lynch syndrome (LS) is the most common inherited cause of colorectal and endometrial cancers. Identifying individuals at risk for LS without personal cancer history requires detailed collection and assessment of family health history. However, barriers exist to family health history collection, especially in historically underserved populations. To improve LS risk assessment in historically underserved populations, we adapted the provider-facing PREdiction Model for gene Mutations (PREMM 5 ™ model), a validated LS risk assessment model, into a patient-facing electronic application through an iterative development process involving expert and patient stakeholders. We report on preliminary findings based on the first 500 individuals exposed to the adapted application in a primary care population enriched for low-literacy and low-resource patients. Major adaptations to the PREMM 5 ™ provider module included reduction in reading level, addition of interactive literacy aids, incorporation of family history assessment for both maternal and paternal sides of the family, and inclusion of questions about individual relatives or small groups of relatives to reduce cognitive burden. In the first 500 individuals, 90% completed the PREMM 5 ™ independently; of those, 94% did so in 5 min or less (ranged from 0.2 to 48.8 min). The patient-facing application was able to accurately classify 84% of patients as having clinically significant or not clinically significant LS risk. Our preliminary results suggest that in this diverse study population, most participants were able to rapidly, accurately, and independently complete an interactive application collecting family health history assessment that accurately assessed for Lynch syndrome risk.

Vaccine Adjuvant Incorporation Strategy Dictates Peptide Amphiphile Micelle Immunostimulatory Capacity - Rui Zhang; Jake S. Kramer; Josiah D. Smith; Brittany N. Allen; Caitlin N. Leeper; Xiaolei Li; Logan D. Morton; Fabio Gallazzi; Bret D. Ulery (The AAPS Journal, 2018)

How do elevated [CO2], warming, and reduced precipitation interact to affect soil moisture and LAI in an old field ecosystem? - Orla Dermody; Jake F. Weltzin; Elizabeth C. Engel; Philip Allen; Richard J. Norby (Plant and Soil, 2007)